Venous blood gas in free-living eastern box turtles (Terrapene carolina carolina) and effects of physiologic, demographic and environmental factors. Issue 1 (25th July 2018) - Adamovicz, Laura; Leister, Katie; Byrd, John; Phillips, Christopher A; Allender, Matthew C
Abstract : Blood gas analysis serves as a useful adjunctive test for health assessment in wildlife, but is infrequently utilized in free-living reptiles. This study demonstrates that box turtle blood gas analytes depend on several physiologic and environmental parameters including season, temperature, packed cell volume and activity level. Abstract: Sustainable wildlife populations depend on healthy individuals, and the approach to determine wellness of individuals is multifaceted. Blood gas analysis serves as a useful adjunctive diagnostic test for health assessment, but it is uncommonly applied to terrestrial reptiles. This study established reference intervals for venous blood gas panels in free-living eastern box turtles ( Terrapene carolina carolina, N = 102) from Illinois and Tennessee, and modeled the effects of environmental and physiologic parameters on each blood gas analyte. Blood gas panels included pH, partial pressure of oxygen (pO2 ), partial pressure of carbon dioxide (pCO2 ), total carbon dioxide (TCO2 ), bicarbonate (HCO3 − ), base excess (BE) and lactate. Candidate sets of general linear models were constructed for each blood gas analyte and ranked using an information-theoretic approach (AIC). Season, packed cell volume (PCV) and activity level were the most important predictors for all blood gas analytes ( P < 0.05). Elevations in PCV were associated with increases in pCO2 and lactate, and decreases in pH, pO2, HCO3 −, TCO2 and BE. Turtles with quiet activity levels had lower pH and pO2 and higher pCO2 than bright individuals. pH, HCO3 −, TCO2 and BE were lowest in the summer, while pCO2 and lactate were highest. Overall, blood pH was most acidic in quiet turtles with elevated PCVs during summer. Trends in the respiratory and metabolic components of the blood gas panel tended to be synergistic rather than antagonistic, demonstrating that either (1) mixed acid–base disturbances are common or (2) chelonian blood pH can reach extreme values prior to activation of compensatory mechanisms. This study shows that box turtle blood gas analytes depend on several physiologic and environmental parameters and the results serve as a baseline for future evaluation.